PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, PENGETAHUAN, DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK - Aini, Nur; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTTaxpayer compliance is one of the problems of the implementationof the self-assessment system. Therefore, the success of tax collection system which uses self-assessment is determined by the level of taxpayer compliance. The purpose of this research is to find out the influence of the modernization tax administration system, tax knowledge, and tax sanction to the tax compliance at Kantor Pelayanan Pajak (KPP) Pratama Bangkalan. This research is a quantitative causal research. The population is the taxpayer, both individual taxpayers and corporate taxpayers which are listed inKantor Pelayanan Pajak (KPP) Pratama Bangkalan. The samples have been determined by using incidental sampling method i.e. the collection of information from the taxpayers who accidentally have met the researchers. 78 respondents have been selected as samples. The data collection methods has been done by issuing questionnaires and the data analysis has been done by using multiple linear regression. The result of the shows that there is positive influence to the modernization of the tax administration system, tax knowledge, and tax sanction to the tax compliance.Keywords:modernization, knowledge, sanctions, taxpayer compliance.